PENGARUH PENAMBAHAN ECO ENZYME BERBASIS LIDAH BUAYA (aloe vera) TERHADAP PERSENTASE KARKAS DAN ORGAN LIMFOID BROILER: EFFECT OF ADDITION OF ALOE VERA BASED ECO ENZYME ON CARCASS PERCENTAGE AND LYMPHOID ORGANS OF BROILERS - Hakim, Insanul; Syukriani, Debby; Sari, Devi Kumala (Universitas Boyolali, 2025)
This study aims to determine the effect and optimal dose in the addition of aloe vera-based eco enzyme in broiler drinking on the percentage of carcasses and lymphoid organs of broilers. This research applies the method of Completely Randomized Design (CRD) 5 treatments and 4 replicates. Details of the treatment applied are as follows; P0 = drinking water without aloe vera eco enzyme solution; P1 = drinking water + 1% aloe vera eco enzyme solution every liter of drinking water; P2 = drinking water + 2% aloe vera eco enzyme solution every liter of drinking water; P3 = drinking water + 3% aloe vera eco enzyme solution every liter of drinking water; P4 = drinking water + 4% aloe vera eco enzyme solution every liter of drinking water. Parameters observed included carcass percentage, lymphoid organ weights (bursa fabricius, thymus, spleen) and mortality. Data processing was tested using the analysis of variance (ANOVA) test. The findings indicated that the addition of aloe vera-based eco-enzyme had no significant effect (P>0.05) on carcass percentage, fabricius bursa weight, thymus, spleen, and mortality. Based on these results, it can be concluded that the provision of aloe vera-based eco enzyme in drinking water at a dose of 1% to 4% per liter of drinking water has no significant effect on carcass percentage, lymphoid organs, and mortality of broilers.